Laser technology in urologic oncology. Issue 3 (August 2022) - Ragonese, Mauro; Dibitetto, Francesco; Bassi, PierFrancesco; Pinto, Francesco
Laser technology has been used in Urology since the 80s with a lot of different applications in endoscopic and open surgery. With the developments of the technology and the introduction of new active medium and source of laser energy, this technology have become the gold standard not only in stone surgery but even in benign prostate enlargement (BPE) surgical treatment. Regarding urologic oncology, laser energy has now reached an important role in focal therapy and in conservative treatment. The possibility of having better functional outcomes without any relevant impact on oncological results led to an increased use of laser in penile surgery, with a significant mention in urological guidelines for this option. In urothelial cancers as well, both in conservative management of upper tract tumors that in the treatment of non muscle invasive bladder cancer, a clear role of these relatively new source of energy have been demonstrated. Finally, both in prostate that in renal cancer the strategy of focal therapy may take advantage from this precise and fine technology. In this review we analyzed and described the applications of laser energy in urological cancers with a specific focus on penile, urothelial and prostate cancer.